Fortification of Citric Acid to Enhance Sensory Properties of Papaya Jam during Storage - Renate, Dharia (Department of Technology of Agricultural product (THP) Jambi University, 2018)
Abstract–The objectives of this research were to know the effect of citric acid on papaya jam to its sensory propertiesduring storage and to determine the concentration of citric acid and storage time to the quality of papaya jam. Material used was mature and ripe of fresh papaya, purchased from local market. This research was designed as a Factorial Completely Randomized Designed. The factors were the concentration of citric acids (0.3, 0.35, 0.4 percent w/w) and storage times (0, 1, 2, 3, 4 weeks). The number of 18 trained panelists evaluated the color, texture, spreadibility and flavor. Data was analyzed using analysis of variance. The significantly different treatment was further analyzed by using Multiple Comparison and TukeyTest. The results indicated that the concentration of citric acids and storage time had significant effects on the quality of papaya jam. Research concluded that the concentration of citric acids of 0.4 percent and storage time of 2 weeks were found to yield the best quality in papaya jam. The papaya jam was good in light yellow color, soft texture, good spreadibility, liked flavor, hence the consumeracceptance like this papaya jam.